Framework for Assessing Urban Energy Sustainability - Vasco-Calle, D (Multidisciplinary Digital Publishing Institute (MDPI), 2021)
The social, economic, and environmental impacts associated with fuels used to power cities cause the sustainability of energy produced and consumed in our urban environment to be constantly challenged. In order to address the issue of urban energy sustainability, we propose a Framework for Assessing Urban Energy Sustainability (FAUES), whose main approach relies on defining a method for determining critical indices associated with the major criteria of sustainable energy generation and consumption. The framework is based on developing a three-step process that integrates historical data regarding energy consumption and production and forecasted parameters on energy sustainability and can be used both in urban energy operations and in planning new urban settlements. The framework was implemented in Brazil as a representative case study, given that its cities lack social inclusion, economic stability, and environmental protection when it comes to energy. The framework functions so that policy makers and managers can assess the sustainability of energy produced and consumed in urban environments on the basis of relevant criteria for the city in which the energy is being evaluated. © 2021 by the authors. Licensee MDPI, Basel, Switzerland.